Organisational capabilities for enhancing the sales quotas development process outcomes for pharmaceutical sales forces - Morelli, Gabriel (Cranfield University, 2009)
The improvement of the sales quotas development process in Spanish pharmaceutical organisations is challenging as the market environment becomes dramatically complex. Setting sales quotas has always been difficult, exemplified by the difficulties in quantifying future sales by sales territory. Extensive research has been conducted and several conceptual models created to facilitate the process of developing sales quotas. Effective management of this process has proved problematic mainly due to difficulties in estimating future sales by territory, the complexity of the systems utilised in the process, the granularity of the data required and the lack of attention to implementation issues. Therefore, determining organisational capabilities that facilitate developing an effective sales quotas process is paramount. This study uses goal setting theory to understand organisational capabilities for the sales quota development process. A sales quota development process for a mid-sized pharmaceutical organisation was examined in terms of activities, which satisfied stakeholders’ expectations. Based on empirical data organisational capabilities were identified and prioritised. Goal setting theory is advanced through the development of the SQD Model that includes a set of sixteen organisational capabilities that are critical for developing an effective sales quotas process for pharmaceutical organisations. This study created the SQP Maturity Framework, a diagnostic tool that allows organisations to assess their sales quota development process and understand which capabilities to acquire or further develop to improve the process. Differences by organisational contexts are highlighted. The focus of this research is the pharmaceutical sector in Spain. The organisational capabilities uncovered and assessed will be relevant to these and other sectors that rely on sales forces. Areas for future research include the replication of this study in different geographies and sectors focusing on identifying more organisational capabilities and routines that facilitate moving organisations towards an optimised level of maturity.